Therapeutic Efficacy of Urethral Sphincteric Botulinum Toxin Injections for Female Sphincter Dysfunctions and a Search for Predictive Factors - Yin-Chien Ou; Kuan-Hsun Huang; Hau-Chern Jan; Hann-Chorng Kuo; Yao-Lin Kao; Kuen-Jer Tsai (Toxins, 2021)
External urethral sphincter (EUS) dysfunction is a common, bothersome female voiding dysfunction. This study aims to analyze the characteristics of different types of female EUS dysfunction, as well as to determine the outcome predictors of sphincteric botulinum toxin A (BoNT-A) injection. Women receiving sphincteric BoNT-A injections for refractory EUS dysfunction were retrospectively reviewed. A comparison of the baseline clinical, urodynamic parameters and the treatment responses were made for patients with different EUS dysfunctions. A total of 106 females were included. Significantly increased detrusor overactivity, detrusor contracting pressure and the bladder outlet obstruction index with decreased urge sensation were noted in patients diagnosed with dysfunctional voiding or detrusor sphincter dyssynergia comparing to those diagnosed with poor relaxation of the external urethral sphincter. The average subjective improvement rate was 67% for the injection. The therapeutic effect was not affected by the type of EUS dysfunction. The multivariate analysis revealed that bladder neck narrowing and catheterization history were predictive of negative outcomes. There is a distinct urodynamic presentation for each type of female EUS dysfunction. Sphincteric BoNT-A injection provides a good therapeutic outcome for refractory EUS dysfunction. A narrowing bladder neck and a history of catheterization suggest poor therapeutic outcomes.